Comparative thermodynamic analyses of Rankine cycles using different working fluids for LNG cold energy recovery - Qiang Liu; Jian Song; Yuanyuan Duan (Case Studies in Thermal Engineering)
This study investigates the impact of condensation temperature on the thermodynamics of Rankine cycles for LNG cold energy recovery using seawater as heat source. The turbine power output is maximized when the LNG temperature at the condenser outlet approaches the pseudocritical temperature at the supercritical pressure, where specific heat peaks. Both evaporation and condensation temperatures are optimized to maximize the net power output considering the limitations of turbine exhaust vapor quality and condensation pressure. The results show that R32 outputs the highest net power, followed by R1270. Although the turbine with R170 generates comparable power to R32, the net power output is 8 % lower due to the highest parasitic power consumption. The cycle using a low critical temperature working fluid requires a more compact turbine with lower inlet volumetric flow rate and smaller evaporator area than that using a high critical temperature fluid. The turbine using R32 offers a moderate size with a higher expansion ratio. R744 requires the least evaporator area and total area for per unit net power, while R32 has the smallest condenser area but requires 78 % more evaporator area than R744.